The Relationship Between Physical Activity and Work-related Stress with The Occurrence of Hypertension in The City of Kendari - Hasanah, Siti Uswatun; Effendy , Devi Savitri; Yunawati, Irma (Universitas Mandala Waluya, 2024)
Hypertension is a serious health problem in the community. This study aims to identify the relationship between physical activity and work stress and the incidence of hypertension in Kendari City, Southeast Sulawesi Province. The research design used was an observational method with a cross-sectional study approach. The sampling technique used was Cluster Random Sampling, with a research focus on seven locations: Kambu Subdistrict Office, Kambu Village Office, Poasia Subdistrict Office, Benu-Benua Village Office, Puwatu Subdistrict, PT Sapta Jaya, and Wua-Wua Post Office. Determination of respondents was carried out using the Purposive Sampling technique, which resulted in 77 respondents. The data obtained were analyzed descriptively using percentages and tested with the Chi-Square test (p-value <0.05). The analysis results showed a significant relationship between physical activity and the incidence of hypertension (p-value = 0.004), as well as between work stress and the incidence of hypertension (p-value = 0.000). In conclusion, physical activity and work stress are factors that trigger the occurrence of hypertension in Kendari City, Southeast Sulawesi Province. It is expected that the people of Kendari City can adopt a healthy lifestyle to improve the quality of health.